Pancreatic Cancer Progression Is Regulated by IPO7/p53/LncRNA MALAT1/MiR-129-5p Positive Feedback Loop - Xu, Jin; Xu, Weixue; Xuan, Yang; Liu, Zhen; Sun, Qinyun; Lan, Cheng (Frontiers in Cell and Developmental Biology, 2021)
Background: Pancreatic cancer is a malignancy with poor prognosis. Importin 7 (IPO7) is a soluble nuclear transport factor, which has been linked to the pathogenesis of several human diseases. However, its role and underlying mechanism in pancreatic cancer are still obscure. Methods: Immunohistochemical (IHC) staining and quantitative real-time polymerase chain reaction (qPCR) were performed to determine IPO7 expression in pancreatic cancer tissues and adjacent tissues. Western blot was used to measure IPO7 expression at protein level in cell lines. CCK-8, BrdU, flow cytometry and Transwell assays were employed to explore the biological functions of IPO7. Subcutaneous xenograft transplanted tumor model and caudal vein injection model in mice were also established to validate the oncogenic role of IPO7. Western blot and qPCR were utilized to detect the regulatory function of IPO7 on p53 and MALAT1, respectively. Interaction between MALAT1 and miR-129-5p, and interaction between miR-129-5p and IPO7 were verified by bioinformatics prediction, qPCR, dual-luciferase reporter gene experiment, RIP and pull-down assay. Results: Upregulation of IPO7 in pancreatic cancer tissues was associated with adverse prognosis of the patients with pancreatic cancer. Knocking down IPO7 remarkably suppressed cancer cell proliferation and metastasis, while promoted apoptosis. Overexpression of IPO7 facilitated the malignant phenotypes of pancreatic cancer cells. Mechanistically, IOP7 could repress the expression of p53, and induce the expression of MALAT1, but reduce miR-129-5p expression. Furthermore, miR-129-5p was identified as a post-transcriptional regulator for IOP7, and its inhibition led to IOP7 overexpression in pancreatic cancer cells. Conclusion: IPO7 is a novel oncogene for pancreatic cancer, and IPO7/p53/MALAT1/miR-129-5p positive feedback loop facilitates the progression of this deadly disease.